Analysis of the Water Balance of the Prumpung River Area (DAS) in Tuban Regency Using the Thornthwaite-Mather Method - Rony Zakariya; Andi Patriadi; Esti Wulandari (Publica Scientific Solution, 2026)
Water is a vital resource whose availability is increasingly uneven due to climate variability, land-use changes, and rising water demand. This condition leads to water surplus during the rainy season and deficit during the dry season, including in the Prumpung Watershed, Tuban Regency. This study aims to analyze the monthly and annual water balance and evaluate the relationship between water availability and water demand in the study area. A descriptive quantitative approach was employed using the Thornthwaite–Mather method, based on rainfall and air temperature data from 2015 to 2024, combined with domestic and non-domestic water demand data for 2024. The results indicate that potential evapotranspiration fluctuates in accordance with air temperature, while actual evapotranspiration is influenced by groundwater availability. Groundwater storage increases during the rainy season and decreases during the dry season. The annual water balance reveals a dominance of deficit conditions in most observation years, although surplus occurs during certain periods. The Prumpung Watershed is vulnerable to water deficits due to uneven rainfall distribution. Sustainable water resource management strategies, focusing on conservation, are required to maintain a long-term hydrological balance.